Nutrition educational interventions for athletes related to low energy availability: A systematic review - DeJong Lempke, A. F.; Reece, L. M.; Whitney, K. E. (PLOS ONE, 2025)
Low energy availability (LEA) is a prevalent concern among athletes, often attributed to intentional or unintentional under-fueling behaviors. Nutritional and energy availability educational interventions are poised for successful LEA prevention, with a robust body of literature examining intervention effectiveness. Thus, this systematic review aimed to synthesize the available evidence on nutritional education interventions to address gaps in nutritional knowledge and combat LEA among athletes. Medical databases (MEDLINE, Web of Science) were systematically searched on July 11, 2023, and an updated search was conducted on July 26, 2024. Studies conducted among adult athletes who underwent nutritional education interventions with assessed effects on dietary knowledge, behaviors, and/or LEA outcomes were included. Study quality was assessed using the Physiotherapy Evidence Database (PEDro) scale by two blinded assessors. Intervention methodology and primary outcomes related to nutritional interventions were extracted by a single assessor. Twelve articles were included (mean PEDro score: 5). Interventions ranged from 1 to 20 sessions, and 10- to 120-minute durations. Most studies employed in-person educational sessions on fueling and macro- and micro-nutrient intake for athletic performance. Half of included studies included LEA education. Intervention approaches were largely heterogeneous, although most programs had favorable outcomes for nutrition knowledge and fueling behaviors. Nutrition interventions appear to be beneficial for athletes in the context of LEA, though current approaches are largely heterogenous. Future research should seek to develop a translational nutritional education plan for broad application in athletes designed to increase nutritional knowledge and combat LEA.